Product and service reliability estimation - Popović Branko Z. (Journal of Engineering Management and Competitiveness, 2019)
Some manufacturers in Europe neglect to determine the reliability of products and services, although reliability is a very significant magnitude of the quality of process results (semi-finished product, product, documentation, service). They usually declare the amount of reliability the way their competitor did, not realizing the real differences between the individual process results, which certainly causes unnecessary costs. When they declare higher reliability, then losses occur due to the high cost of customer complaints, and when they declare lower reliability, then losses arise due to large losses in demand for the results of market processes. In America, a different approach is taken to consider reliability, which involves designing, planning, and verifying the reliability of process results, using special computer programs and electronic computers. Reliability design allows defining the reliability of systems and components of process results, according to the requirements of critical quality characteristics, thereby achieving the required level of quality. Reliability planning enables the preparation of reliability checks by developing a test plan, reliability and warranty plan, a forecasting plan and a product or service guarantee plan. The reliability check makes it possible to determine the true reliability of the results of the process after experimental testing, under long-term real conditions or under short-term accelerated conditions, with the application of certain higher loads. This paper discusses the elements of stability and reliability and proposes the necessary procedure for selecting the design, planning and checking the reliability of process results. Using this selection, the procedures for designing, planning, and verifying the reliability of certain process results are shown here.